Effects of Wait Time when Communicating with Children who have Sensory and Additional Disabilities. (September 2013) - Johnson, Nicole; Parker, Amy T.
Introduction: This study utilized wait-time procedures to determine if they are effective in helping children with deafblindness or multiple disabilities that include a visual impairment communicate in their home. Methods: A single subject with an alternating treatment design was used for the study. Zero- to one-second wait time was utilized before prompting for a response during three baseline sessions. This was compared to 5-, 10-, and 15-second wait-time increments used during six intervention sessions. Three participants with visual impairments, developmental disabilities, and communication delays participated in the study. One of the participants was deafblind. Results: All three participants responded twice as often during intervention phases as in baseline sessions. The results showed that 5-, 10-, and 15-second wait times were effective when reciprocally communicating with children who have multiple disabilities with a visual impairment or deafblindness. Discussion: The findings of this study determined that wait time was effective and showed promising results for children with deafblindness or multiple disabilities. The study indicated that such children need time to process what is being asked in order to respond appropriately. Prompting quickly can frustrate the child with disabilities. Limitations of the study included heterogeneity and fragile medical condition of the participants, distractions, and the need for future research on the use of this technique. Implications for practitioners: By utilizing at least five seconds of wait time, parents and educators may be able to see an increase in appropriate responses from the child. Wait-time interventions could increase opportunities for learning, social interaction, and communication, and are easily implemented with little to no training.